Differential expression of vasopressin alleles in the Brattleboro heterozygote - Sherman, TG (J Neurosci, 1988)
A solution hybridization/RNase protection assay for the molar quantitation of vasopressin and oxytocin mRNAs, using synthetic complementary RNA probes, is described. This assay was optimized to permit the identification of vasopressin (AVP) mRNAs containing the frame-shift point deletion causing inheritable diabetes insipidus in the Brattleboro strain of rat. Examination of RNA from hypothalamic magnocellular tissue punches found that of the 86.1 x 10(-18) mol [86.1 attomoles (amol)] of AVP mRNA detected in the Brattleboro heterozygote paraventricular (PVN) nucleus, 5.2% could be shown to be mutant AVP mRNA (AVPd RNA). The percentage of AVPd RNA increased dramatically to 18.1% after 6 d of chronic intermittent salt-loading. Similar percentages and percentage increases of AVPd RNA were detected in the heterozygote supraoptic nucleus (SON). These values were contrasted with those found in parallel studies in both Long Evans and Brattleboro homozygotes, and compared with values for oxytocin (OT) mRNA in all 3 AVP rat genotypes. The results of continued osmotic regulation of the mutant AVP gene, the low native levels of AVPd RNA found in both the Brattleboro heterozygote and homozygote, and the magnitudes of AVPd expression change with chronic osmotic challenge were interpreted as indicating that (1) in the diploid rat genome, both AVP alleles are transcribed, (2) the osmotic regulation of the mutant AVP gene is normal, and (3) the low levels of AVPd mRNA are consistent with a shorter-than-control effective mRNA half-life.